Dielectric constant of the polarizable dipolar hard sphere fluid studied by Monte Carlo simulation and theories - Valisko, M.; Boda, D. (Condensed Matter Physics, 2005)
A systematic Monte Carlo (MC) simulation and perturbation theoretical
(PT) study is reported for the dielectric constant of the polarizable dipolar
hard sphere (PDHS) fluid. We take the polarizability of the molecules
into account in two different ways. In a continuum approach we place the
permanent dipole of the molecule into a sphere of dielectric constant Ɛ∞
in the spirit of Onsager. The high frequency dielectric constant Ɛ∞ is calculated
from the Clausius-Mosotti relation, while the dielectric constant of
the polarizable fluid is obtained from the Kirkwood-Frohlich equation. In the molecular approach, the polarizability is built into the model on the molecular
level, which makes the interactions non- pairwise additive. Here we
use Wertheim’s renormalized PT method to calculate the induced dipole
moment, while the dielectric constant is calculated from our recently introduced
formula [22]. We also apply a series expansion for the dielectric
constant both in the continuum and the molecular approach. These series
expansions ensure a better agreement with simulation results. The agreement
between our MC data and the PT results in the molecular approach
is excellent for low to moderate dipole moments and polarizabilities. At
stronger dipolar interactions ergodicity problems and anizotropic behaviour
appear where simulation results become uncertain and the theoretical approach
becomes invalid. Приведено результати систематичного вивчення методом Монте Карло (МК) та теорії збурень (ТЗ) діелектричної сталої рідини поляризаційних дипольних твердих сфер. Поляризація молекул враховується двома способами. У підході неперервного середовища постійний диполь молекули поміщається у сферу з діелектричною
сталою Ɛ∞, так як це робиться Онзагером. Високочастотна діелектрична стала Ɛ∞ рахується зі співвідношення Клаузіса-Мозотті,
тоді як діелектрична стала поляризаційної рідини отримується з
рівняння Кірквуда-Фройліха. У молекулярному підході поляризація враховується на молекулярному рівні, внаслідок чого взаємодії
не є парно адитивними. Для розрахунку індикованого дипольного моменту використовується ренормалізаційний метод ТЗ Вертхайма, а для діелектричної сталої використовується оригінальна
формула [22]. Ми також застосовуємо групові розклади для діелектричної сталої в обох підходах. Групові розклади забезпечують
кращу узгодженість з комп’ютерними результатами. Узгодженість
між МК даними і результатами ТЗ є дуже доброю у діапазоні
низьких та середніх дипольних моментів та поляризації. Для сильних дипольних взаємодій проявляються проблеми ергодичності
та анізотропної поведінки і комп’ютерні дані стають сумнівними, а
теоретичні результати – необгрунтованими.